Medical treatment : decisions and the law - Johnston, Christopher; Roper, Sophia (London [England] : Bloomsbury Professional, 2022)
"This leading textbook is aimed at lawyers, judges, health care practitioners and local authority professionals who have to deal with the most ethically challenging cases which face the courts: medical treatment decisions. It offers a practical, readily accessible text for those dealing with providing medical treatment to those without capacity in real life. The book provides not only a clear description of the legal principles applied by Court of Protection judges and the arguments deployed by the authors in the many Court of Protection cases in which they appear, but also a large number of precedents and appendices which will ease the preparation for court hearings (which are often heard as an emergency). Key developments include: - New Fertility Issues chapter -including contraception, sterilisation, and abortion - Chapter 13 changed from PVS/MCS to "Withdrawal of treatment" - the case law has widened on this - Discussion of "Escalation of Care" - the clinical question of whether treatment should be made available - covering matters including NICE guidelines and care pathways. Issues around availability of treatment on clinical grounds are increasing in case law - Expansion of Chapter 17 to cover the funding of treatment. - New chapter on mental health/compulsory treatment other than MHA 1983: there are a range of areas where people can be compelled to have treatment on public health grounds - such as the Coronavirus Act, but also quarantine laws, applications in the magistrates to compel treatment for infectious diseases such as TB, and vaccinations."--
Part 1: General Principles -- 1. Consent - general -- 2. Consent - adults -- 3. Deciding for others - adults -- 4. Deciding for others - children -- 5. Going to court -- 6. Restraint and deprivation of liberty Part 2: Specific Problems -- 7. Sterilisation -- 8. Abortion -- 9. Assisted reproduction -- 10. Managing pregnancies -- 11. Feeding -- 12. Religious objections to treatment -- 13. Permanent vegetative state and minimally conscious states -- 14. Treatment of suicidal patients -- 15. The end of life -- 16. Human organ and tissue donation -- 17. Access to Healthcare -- 18. Mental health and compulsory treatment
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Medical laws and legislation -- Great Britain; Electronic books